Combined neuromuscular electrical stimulation and transcutaneous spinal direct current stimulation increases motor cortical plasticity in healthy humans - Koseki, Tadaki; Kudo, Daisuke; Yoshida, Kaito; Nito, Mitsuhiro; Takano, Keita; Jin, Masafumi; Tanabe, Shigeo; Sato, Toshiaki; Katoh, Hiroshi; Yamaguchi, Tomofumi (Frontiers in Neuroscience, 2023)
Introduction Neuromuscular electrical stimulation (NMES) induces neural plasticity of the central nervous system (CNS) and improves motor function in patients with CNS lesions. However, the extended stimulus duration of NMES reduces its clinical applicability. Transcutaneous spinal direct current stimulation (tsDCS), which increases afferent input, may enhance the effects and reduce the stimulus duration of NMES. This study investigated the excitability of the motor cortex, somatosensory cortex, and spinal motor neurons after the combined stimulation of NMES and tsDCS. Methods Among the 55 participants in this study, 24 were allocated to experiment 1, 15 to experiment 2, and 16 to experiment 3. They received intervention for 20 min on different days: (1) NMES combined with tsDCS (NMES + tsDCS), (2) NMES combined with sham tsDCS (NMES + sham tsDCS), and (3) sham NMES combined with tsDCS (sham NMES + tsDCS). NMES was delivered to the right common peroneal nerve at 25 Hz with the intensity at 120% of the motor threshold. For tsDCS, the cathodal electrode was positioned on the thoracic 10th–12th vertebral levels, and the anodal electrode was located on the right shoulder. The stimulus intensity was 2.5 mA. In experiment 1, motor evoked potentials (MEPs) and short-latency intracortical inhibition (SICI) were measured by transcranial magnetic stimulation up to 60 min after stimulation. The spinal motor neurons’ excitability was assessed by recording the posterior root muscle reflex (PRMR) induced via transcutaneous spinal cord stimulation in experiment 2, and the primary somatosensory cortex excitability was evaluated by recording the somatosensory evoked potentials (SEPs) in experiment 3 up to 15 min after stimulation. Results Compared to before the stimulation, NMES + tsDCS significantly increased MEP for 60 min or more, and significantly decreased SICI immediately after. Conversely contrast, the PRMR significantly decreased immediately after, and SEPs were unchanged. Discussion These results suggest that simultaneous afferent inputs from different stimulus positions critically induce primary motor cortex plasticity. The combined stimulation of NMES with tsDCS may facilitate the development of a new neurorehabilitation technique.